Public Service Innovation Hajj Pilgrimage Elderly Friendly 2024 Kemenag RI - Mu’minah, Sulton; Purwanto Edi, Abdul Ghoni; A.M.H. Marasabessy; Nurdin, Ismail (Celebes Journal of Community Services, 2025)
This study aims to explore the implementation of the 2024 “Elderly Friendly Hajj” program initiated by the Ministry of Religious Affairs of the Republic of Indonesia. The program is designed to meet the specific needs of elderly pilgrims, who make up 21% of Indonesia's total pilgrims. Using a case study approach, this research collected data through semi-structured interviews, field observations, and analysis of official documents. Data analysis was conducted thematically using NVivo software based on the New Public Management (NPM) theoretical framework. The results showed that the integration of digital technologies, such as the Hajj companion application and health information system, significantly improved service quality. Segmentation of pilgrims based on the level of independence proved effective in optimizing resources and improving efficiency. However, the main challenges faced are limited trained labor as well as logistical constraints, including pilgrim density and extreme temperatures. The conclusions of this study emphasize the importance of technological innovation, workforce training, and multi-actor collaboration to ensure program sustainability. The “Elderly Friendly Hajj” program can be a relevant model of inclusive public services at the global level by applying NPM principles of efficiency and responsiveness.